2020
DOI: 10.1680/jgeen.18.00243
|View full text |Cite
|
Sign up to set email alerts
|

Behaviour of cement-stabilised silty sands subjected to harsh environmental conditions

Abstract: The present study evaluates the effect of three distinct amounts of fines, Portland cement and dry unit weights on the accumulated loss of mass (ALM), maximum shear modulus at small strains (G 0) and tensile strength (q t) of stabilised sands subjected to wet-dry cycles. Tensile strength test results showed that addition of fines to a sand stabilised with cement increased its tensile strength, irrespective of the dry unit weight ( d) and cement amount present in the mixture. Increasing the amounts of fines of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 17 publications
0
3
0
1
Order By: Relevance
“…Therefore, the durability of chemically stabilised soils depends on several factors, including the mineralogical and physicochemical constituents of the soil, the amount of chemical additives added to the soil, and several environmental factors. Considerable research has shown that climatic and environmental factors majorly affect the durability and engineering performance of cement-and limestabilised subbase and subgrade materials, leading to the deterioration and reduction in the service life of flexible pavements [51,53]. Numerous cases of deterioration in chemically stabilised pavement interlayers and embankments founded on floodplains have been attributed to leaching that removes the stabilising effect of the chemical additives via rainfall-induced water ingress.…”
Section: Influence Of Water Ingress On the Durability Of The Lime-stabilised Lateritic Soilmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the durability of chemically stabilised soils depends on several factors, including the mineralogical and physicochemical constituents of the soil, the amount of chemical additives added to the soil, and several environmental factors. Considerable research has shown that climatic and environmental factors majorly affect the durability and engineering performance of cement-and limestabilised subbase and subgrade materials, leading to the deterioration and reduction in the service life of flexible pavements [51,53]. Numerous cases of deterioration in chemically stabilised pavement interlayers and embankments founded on floodplains have been attributed to leaching that removes the stabilising effect of the chemical additives via rainfall-induced water ingress.…”
Section: Influence Of Water Ingress On the Durability Of The Lime-stabilised Lateritic Soilmentioning
confidence: 99%
“…Although significant improvements in strength and stiffness of tropical residual soils treated with lime and other calcium-based additives have been reported, their durability and long-term stability under harsh environmental conditions have not been fully understood. Some researchers reported that the durability of chemically-stabilised soils tends to decrease with time under certain climatic conditions such as freeze-thaw cycles [9,49], wetting-drying cycles [50,51], and leaching via continuous water circulation [52,53]. Leaching-induced deterioration of chemically stabilised subbases and subgrades occurs as a result of rainfall-induced water ingress into pavement structural layers, which adversely modify the physicochemical characteristics of the stabilised material by the gradual removal of the chemical constituents of the stabiliser.…”
Section: Introductionmentioning
confidence: 99%
“…Selain mampu meningkatkan sifat mekanis tanah, semen juga dapat membantu mengikat tanah dengan partikel karet. (Consoli et al, 2019) dalam penelitiannya menguji berbagai campuran agregat halus ke pasir berlanau yang diolah semen. Penelitian tersebut menunjukkan bahwa berat volume kering tanah (γd) meningkat dari 15,5 menjadi 16,5 kN/m³ dan meningkatkan modulus geser pada regangan kecil (G0) sekitar 50% pada spesimen tanah pasir berlanau.…”
Section: Pendahuluanunclassified
“…Whereas there are studies in literature that have reported on the effects of fines on the behavior of un-cemented sand, such studies on cement-treated sand are very rare. Recently, Consoli et al [6] has explored the effects of fine particles in cemented sand and reported that presence of fine particles increase the tensile strength and stiffness of the material. However, the fine contents considered in the study were silt sized particles in large proportion (i.e., 10-30%).…”
Section: Introductionmentioning
confidence: 99%